Peningkatan Sikap Nasionalisme Melalui Mata Pelajaran Sejarah di Kelas X DKV SMK Cokroaminoto Kotamobagu - Kodarasi, Febri; Umbase, Ruth Sriana; Pangkey, Itje (Abdurrauf Science and Society, 2025)
This study aims to determine and analyze the increase in nationalism attitudes through history subjects in class X students of SMK Cokroaminoto Kotamobagu. The main focus of the study includes understanding students' nationalism attitudes, the role of history teachers, obstacles faced, and efforts made to instill nationalism. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study were class X students and history teachers at SMK Cokroaminoto Kotamobagu. The results of the study indicate that students' nationalism attitudes still need to be improved, as seen from the low participation in activities that reflect love for the country. The role of teachers is very important in instilling nationalist values ??through history teaching methods that touch on students' emotional and intellectual aspects. The main obstacles in fostering nationalism come from the influence of globalization, foreign cultures, and lack of student discipline. Efforts made include increasing history learning activities that contain national values, strengthening the role of teachers as motivators, and involving students in activities that foster a spirit of nationalism. This study suggests that collaboration between schools and parents be strengthened in shaping students' nationalist character. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis peningkatan sikap nasionalisme melalui mata pelajaran sejarah pada siswa kelas X SMK Cokroaminoto Kotamobagu. Fokus utama penelitian mencakup pemahaman tentang sikap nasionalisme siswa, peran guru sejarah, kendala yang dihadapi, serta upaya yang dilakukan untuk menanamkan nasionalisme. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Subjek penelitian adalah siswa kelas X dan guru sejarah di SMK Cokroaminoto Kotamobagu. Hasil penelitian menunjukkan bahwa sikap nasionalisme siswa masih perlu ditingkatkan, terlihat dari rendahnya partisipasi dalam kegiatan-kegiatan yang mencerminkan cinta tanah air. Peran guru sangat penting dalam menanamkan nilai-nilai nasionalisme melalui metode pengajaran sejarah yang menyentuh aspek emosional dan intelektual siswa. Kendala utama dalam menumbuhkan nasionalisme berasal dari pengaruh globalisasi, budaya asing, dan kurangnya kedisiplinan siswa. Upaya yang dilakukan antara lain adalah peningkatan kegiatan pembelajaran sejarah yang bermuatan nilai kebangsaan, penguatan peran guru sebagai motivator, serta melibatkan siswa dalam kegiatan yang menumbuhkan semangat nasionalisme. Penelitian ini menyarankan agar kolaborasi antara sekolah dan orang tua diperkuat dalam membentuk karakter nasionalis siswa. Kata kunci: Peningkatan,  Sikap Nasionalisme, Mata Pelajaran Sejarah